Improving Restaurant Employee Performance Through Assistant Manager Communication at Amber Resort Beach Central, Lombok - Mandra (Faculty of Economics and Business, University of Mataram, 2023)
The aim of this research is to find out the condition of the performance of Amber Beach Resort Lombok restaurant employees and to find out how to improve employee performance through communication with the assistant manager of Amber Beach Resort Lombok. The research design used is descriptive qualitative, which emphasizes analysis of inference processes based on the phenomena that occur in the field, with data collection using observation, interview, and documentation methods. Based on the results of the research that has been done, the performance of current employees is good and in accordance with the applicable sop where employees arrive on time, use uniforms neatly and that have been determined, employees are willing to get overtime hours (over time), able to achieve the target of providing the amount of food, able to provide good service, can cooperate between employees and guests of Amber Beach Resort Lombok.